Investment under liquidity constraints and uncertainty: investigating the effects of irreversibility - Δράκος Κωνσταντίνος; Γούλας Ελευθέριος; Καλλανδράνης Χρήστος (SPOUDAI Journal of Economics and Business, 2006)
Irreversibility affects investment spending via two channels, a) financial constraints and b) uncertainty. According to our results, the impact of cash flow is accentuated for sectors facing higher irreversibility, implying that their investment spending is more sensitive to internal funds. In addition, the investment-uncertainty derivative is of larger magnitude for the group of sectors facing higher irreversibility. JEL Classifications: C23; E22; G31